Mecanismo de transporte iônico em íleo de coelho, induzido por microcistina LR de Microcystis aeruginos : participação de macrófagos,Il-1beta, TNFalpha e mediadores pró-inflamatórios - Jimenez, George Chaves (2003)
This work as main objective to evaluate the eletrogenic effect in preparations of íleum of rabbit fixes in chambers of Üssing, in presence of supernatant of macrophages (S.MfS), stimulated with microcistin-LR (MCLR), of Microcystis aeruginosa. S.MfS estimulated with MCLR (3,2.10-7M; 9,6.10-7M e 3,2.10-6M), produces effect secretion, of the form dose-dependent; being that short circuit current (Isc), the secular chain variation (t) can be described for an equation of the type Isc = a . ekt for a correlation coefficient r = 0,9988 and Iscmaximo = 128,16 ± 14,54 µA . cm-2. Later, was observed that the metabolic processes associates’ geneses of the FSI, from stimulated macrophages, require the participation of a protein G, sensible pertussis active toxin. It was also verified that inhibing of protéic synthesis, proteases, phosfolipase A2, ciclooxigenases, lipoxigenases, synthesis TNF-a, and antagonists of the PAF, they had reduced the FSI synthesis. With the application of monoclonal antibodies, it was verified that interleukin-b (IL-1b), was the main FSI; as also, that macrophages stimulated with MCLR, in the concentrations above, produced IL-1b and TNF-a, of form dose-dependent. The pay-treatment of the ileum mucosal with bumetanide, indomethacin, tetrodotoxin and HOE, disclosed that the secretory effect, by means of stimulated action of the S.MfS with MCLR is dependent of the secretion of ions chloride, with the participation of PAF, prostaglandins and mediators of the enteric nervous system. With this effect, it associates reduction of the transepitelial resistance (Rte), also mediated for prostaglandins, TNF-a, and indirectly IL-1b. The analysis of the coefficient of Hurst, disclosed that these effect had not occurred of random form, but had involved significant alterations in the kinetic parameters of the eletrogênic effect, to the level of the ileum mucosal. Macrophages stimulated for MCLR, produces and liberate more TNF-a of that IL-1b, to the Constant taxes, being this a linked characteristic to the type of employed stimulation. It is concluded, therefore, that MCLR stimulates macrophages to produce substances that can act as intestinal secretion factor, to the level of the ileum mucosal, involving chloride canals, reduction of the Rte, requesting for this, the participation of pro-inflammatory mediators and the enteric nervous system.